KEPASTIAN HUKUM ATAS PEMOTONGAN PAJAK OLEH WAJIB PAJAK DALAM NEGERI TERHADAP WAJIB PAJAK LUAR NEGERI - Ali Hakim; Khalimi Khalimi (Jurnal Ilmiah Global Education, 2022)
The purposes of this study are to analyze and understand legal remedies that can be taken by WPDN in obtaining legal certainty regarding their obligation to make withholding tax on their income to WPLN as well as to analyze and understand legal certainty for WPDN in carrying out the obligation to withhold tax on income to WPLN based on regulations. applicable taxation. The method used in this author is normative juridical research supported by a statute approach, a conceptual approach, and a case approach based on primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials is obtained through studies or studies of laws and literature research as well as Court decisions and Supreme Court decisions which researchers analyze in a systematic way. The results of this study indicate that the application of the Double Tax Avoidance Agreement (P3B) is caused by administrative problems that create legal uncertainty that is not in accordance with the purpose of the law (tax treaty). PT. Westcon Internasional Indonesia has fulfilled the tax administration requirements, namely the principle of source, nationality, and domicile principles in accordance with the basic tax law.